2010
DOI: 10.1158/0008-5472.can-10-1590
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Hsp90 Cochaperone p23 Promote Tumor Progression and Poor Prognosis in Breast Cancer by Increasing Lymph Node Metastases and Drug Resistance

Abstract: Abstractp23 is a heat shock protein 90 (Hsp90) cochaperone located in both the cytoplasm and nucleus that stabilizes unliganded steroid receptors, controls the catalytic activity of certain kinases, regulates protein-DNA dynamics, and is upregulated in several cancers. We had previously shown that p23-overexpressing MCF-7 cells (MCF-7+p23) exhibit increased invasion without affecting the estrogen-dependent proliferative response, which suggests that p23 differentially regulates genes controlling processes link… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 49 publications
(59 reference statements)
7
60
1
Order By: Relevance
“…In summary, HSP90 has been linked to chemoresistance in different clinical settings including breast cancer [36][37][38][39][40][41].The described study of Song et al [29] corroborates the observations that low HSP90 expression is a positive prognostic feature. In our study we pinpointed the predictive aspect of the association of HSP90 with proliferation markers and its association with the higher response to chemotherapy.…”
Section: Discussionsupporting
confidence: 66%
“…In summary, HSP90 has been linked to chemoresistance in different clinical settings including breast cancer [36][37][38][39][40][41].The described study of Song et al [29] corroborates the observations that low HSP90 expression is a positive prognostic feature. In our study we pinpointed the predictive aspect of the association of HSP90 with proliferation markers and its association with the higher response to chemotherapy.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, expression of p23 correlates with breast tumor grades, and it is highly overexpressed in malignant metastatic tissues. Importantly, microarray analysis using breast cancer cell line MCF7 showed that overexpression of p23 changes the expression levels of several genes involved in metastasis and drug resistance (29), and p23 is required for optimal cell mobility and invasion (36). Recent global analysis of p23 functions by Echtenkamp et al (47) suggests an extensive cellular network through which p23 modulates a wide range of physiological functions in a manner dependent and independent of Hsp90.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Overexpression of these stress response proteins is observed in various cancers and linked, in some cases, to poor prognosis and resistance to chemotherapeutic treatment. 42,43 As the mitochondrial ATP-dependent Lon protease plays a similar role, assisting cells to survive and adapt to various proteotoxic stresses that are linked to oncogenesis (eg, hypoxic, oxidative, and ER stress), 10,11,15 we speculated that Lon might also be a potential anticancer drug target. For personal use only.…”
Section: Discussionmentioning
confidence: 99%